Why Digital Virality Failed to Produce Electoral Victory: A Gramscian Analysis of Amin’s 2024 Presidential Campaign - Fadhilah Permata Nira; Ganjar Widhiyoga (Jurnal Spektrum Komunikasi, 2026)
During the 2024 Indonesian Presidential Election, a distinct form of support emerged for Presidential Candidate Pair Number 01-Anies Baswedan and Muhaimin Iskandar (AMIN). This viral support originated on the X platform (formerly Twitter) through accounts such as @aniesbubble, @olppaemiproject, and @humaniesproject. These accounts described themselves as a grassroots volunteer movement driven by concerns regarding the prevailing domestic political dynamics. Consequently, they sought to conduct civic education and digital campaigning by packaging political information with a K-pop style to make it more engaging. This approach was chosen due to their affinity for K-pop and the belief that conveying ideological messages in this manner would yield significant impact, despite their lack of the vast resources available to other candidate pairs. Their digital efforts successfully generated considerable attention and popularity on social media, particularly on X. However, this momentum did not translate into a victory for AMIN, as they ultimately secured approximately 24% of the vote. This electoral defeat is viewed as a failure of the counter-hegemony attempt in the sense of Antonio Gramsci’s organic intellectuals undertaken by these groups. This study employs an explanatory qualitative method utilizing both primary and secondary data. The findings indicate that the counter-hegemonic efforts by @aniesbubble, @olppaemiproject, and @humaniesproject on X failed to challenge the consensus established by the bourgeois-aligned forces backing Candidate Pair 02. The latter possessed superior resources, including political party coalitions, incumbent support, substantial campaign funding, and the use of influencers, celebrities, and public figures.